Withdrawal from the Consent to Process Personal Data Provided as Counter-Performance: Contractual Consequences - Kull, Irene (Journal of the University of Latvia. Law, 2020)
This article deals with the Directive (EU) 2019/770 of the European Parliament and of the Council of 20 May 2019 on certain aspects concerning contracts for the supply of digital content and digital services. The Directive says that Member States are free regarding the question of the legal nature of contracts for the supply of digital content or digital services. The Directive must be transposed into national law by 1 July 2021 and the date of entry into force of the transposition rules shall be 1 January 2022. As contracts for the supply of digital content and digital services were not previously regulated, the major challenges for Member States are the contractual meaning of personal data and categorisation of these contracts. The article explores the link between consumer consent to process personal data and the contractual consequences of withdrawal from such consent, specifically the trader’s right to terminate the contract. The author supports the need to grant traders the right to terminate the contract in order to provide balance between the rights and obligations of the parties in accordance with the existing national law.